Rwanda : Fifth Review Under the Policy Support Instrument and Request for Extension, and Request for an Arrangement Under the Standby Credit Faciltity-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the economic performance of Rwanda. Despite an unfolding external shock, growth in Rwanda remained strong in 2015. Real GDP grew by an estimated 6.9 percent in 2015, buoyed by strong construction and services activity, and leading indicators suggest continued robust growth in the first quarter of 2016. However, in the absence of policy adjustment already underway, growth would remain at its potential, but the balance-of-payment situation would be unsustainable. The authorities are requesting to extend the current Policy Support Instrument (PSI)-supported program. The authorities believe the PSI framework has served well in anchoring their medium- and long-term growth and reform agenda, and signaling policy intentions and performance to investors and development partners.